PWE-059 Earlier discharge for inflammatory bowel disease flare-ups responding to intravenous hydrocortisone?. (17th June 2017) - Wood, JA; Umar, N; Hebden, JM
Abstract : Introduction: Patients with a severe flare-up of their inflammatory bowel disease (IBD) are usually treated in hospital with a course of intravenous hydrocortisone (ivHC). Responders are typically converted to oral prednisolone (oP) and observed for a variable time period before discharge on a reducing course of steroids. We questioned whether the in-hospital observation period on oP is necessary and therefore whether we could safely reduce length of stay. Method: Patients admitted with a flare-up of their IBD were identified from ICD10 coding records (K50.0, K50.1, K50.8, K50.9, K51.3, K51.9, AO9.9). Hospital records were then identified on the electronic discharge management system (EDMS) and the Integrated Clinical Environment (ICE). Demographics, length of stay (LoS), time on ivHC and oP, haematology and biochemistry including C-reactive protein (CRP), and biological treatments were collected. Results: One hundred and thirteen patients were admitted for a flare-up of their IBD during 2016. Fifteen records were unavailable, 23 patients were excluded as they did not receive ivHC or oP, 8 patients went to surgery whilst still on ivHC; leaving 67 patient records for analysis (41 females, median age of 32 (17-79)). The LoS (median (range)) was 7 (3–20*) days with 4.5 (1–14) days on ivHC and 2 (0–14*) days on oP prior to discharge. *One patient who was deemed fit for discharge from their IBD flare-up stayed a further 51 days in hospital after transfer to another specialty and was excluded from the data. The median laboratory values during the hospital stay are shown in the table: Only 1/67 (1.49%) patient relapsed after conversion to oP while still in hospital and required further ivHC. This patient was found to have co-infection with cytomegalovirus (CMV) and responded to ivHC and ganciclovir. The 30 day readmission rate for the other 66 patients was 3 (4.55%). These 3 individual patient admissions were due to co-infection with CMV 3 days post discharge, a flare-up 4 days post discharge requiring infliximab (CRP 151.9 on discharge) and a further flare-up 26 days post discharge requiring ivHC. Six patients were commenced on biologic treatment (3 on vedoluzimab, 2 on infliximab and 1 on adalimumab) during their in-patient stay. Their LoS was a 9 (5–20) days and was not significantly longer than those not treated with biologics (p=0.10) with 6.5 (2–10.5) days on ivHC and 3 (1–14) days on oP. Conclusion: Our retrospective survey suggests that it is safe to discharge patients with a flare-up of their IBD on the day that the decision is made to convert from ivHC to oP. Such a policy would reduce length of stay by a median of 2 days. Disclosure of Interest: None Declared